PERANCANGAN SISTEM INFORMASI AKUNTANSI ASET TETAP DESA BERBASIS WEB (PILOT PROJECT PADA KECAMATAN KOTA SIGLI) - Mukrim, Mukrim; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
Fixed assets are one important element in financial statements. Handling of fixed assets that are not appropriate or not in accordance with PSAP 07 will have an effect on financial reporting. Improper handling of fixed assets due to still practicing a manual system, which allows for various problems in financial reporting. This study aims to design an information system for recording fixed assets to assist village officials in recording assets and for reporting fixed assets. The system designed in this research is Web-based, using PHP as a programming language. This study uses a case study method, data collection techniques in research conducted interviews, observations, and literature studies conducted directly with the village apparatus. This research resulted in an application system that facilitates future village apparatuses